2020
DOI: 10.1002/adhm.202000690
|View full text |Cite
|
Sign up to set email alerts
|

Internally Responsive Nanomaterials for Activatable Multimodal Imaging of Cancer

Abstract: Advances in technology and nanomedicine have led to the development of nanoparticles that can be activated for multimodal imaging of cancer, where a stimulus induces a material modification that enhances image contrast. Multimodal imaging using nanomaterials with this capability can combine the advantages and overcome the limitations of any single imaging modality. When designed with stimuli‐responsive abilities, the target‐to‐background ratio of multimodal imaging nanoprobes increases because specific stimuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 101 publications
0
33
0
Order By: Relevance
“…The development of stimuli-responsive organic fluorescent materials has received tremendous attention as a result of their fundamental research and promising applications in information storage, 1,2 anti-counterfeiting paper, 3,4 sensors [5][6][7] and bioimaging. [8][9][10] In particular, mechanochromic (MC) materials that use mechanical force as a stimulus have been recognized as ideal candidates for preparing anti-counterfeiting labels and pressure-sensitive devices. [11][12][13] Compared to inorganic MC materials, organic MC materials have a number of key advantages, such as abundant synthetic techniques, low preparation costs and functional diversity.…”
Section: Introductionmentioning
confidence: 99%
“…The development of stimuli-responsive organic fluorescent materials has received tremendous attention as a result of their fundamental research and promising applications in information storage, 1,2 anti-counterfeiting paper, 3,4 sensors [5][6][7] and bioimaging. [8][9][10] In particular, mechanochromic (MC) materials that use mechanical force as a stimulus have been recognized as ideal candidates for preparing anti-counterfeiting labels and pressure-sensitive devices. [11][12][13] Compared to inorganic MC materials, organic MC materials have a number of key advantages, such as abundant synthetic techniques, low preparation costs and functional diversity.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, tumor microenvironment (TME)‐responsive smart therapy systems have attracted increasing attention in the field of cancer therapy because they can take advantage of the difference between tumor and normal tissue microenvironments, thus decreasing side effects. [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ] The TME exhibits several distinguishable physiological features such as mildly acidic pH, hypoxia, high level of reactive oxygen species (ROS), excess levels of GSH, and overexpression of specific enzymes. [ 1 , 2 , 3 , 4 , 5 ] These features can be exploited as stimuli to induce specific changes in the chemical structures or physical properties of drugs to realize tumor‐specific treatment with less side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Contrast agents (CAs) play an essential role in obtaining accurate diagnosis results for the current magnetic resonance imaging (MRI) technology [ 1 4 ]. The majority of MRI CAs are derived from paramagnetic (Gd 3+ and Mn 2+ ) or superparamagnetic (Fe 3 O 4 ) metallic materials [ 5 10 ]. However, metal-associated toxicity has raised concerns over the use of these metal-based CAs [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…From our recent study and other reported studies, ideal nitroxides-based mCAs should meet the following requirements simultaneously: (1) they are amphiphilic to self-assemble into stable nano-sized structures; (2) the content of nitroxides in mCAs should be high enough for enhancing the imaging contrast; (3) they should have structural flexibility for rapid energy exchange and sufficient contact between the paramagnetic center and the surrounding water molecules; and (4) they should have excellent biodegradability to reduce toxicity of macromolecules in mCAs [ 10 , 17 , 25 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%